2022
DOI: 10.1039/d2ta02289c
|View full text |Cite|
|
Sign up to set email alerts
|

Direct ink writing of high-performance Bi2Te3-based thermoelectric materials using quasi-inorganic inks and interface engineering

Abstract: Direct ink writing offers a unique solution for constructing shape-controllable devices. In this way, thermoelectric (TE) devices can optimize the power generation from industrial waste heat in the design of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Figure 6(a) illustrates the fabrication process of the conformal TEG and demonstrates how 3D printing was employed to produce semicircular shapes corresponding to the cylindrical heat source. Several studies have reported the production of such conformal TEGs [32,42,52,55,71,95], with a representative example being the work by Kim et al [32], who created cylindrical TEGs with dispenser-printed n-and p-type half-rings using an all-inorganic TE ink (figure 6(b)). The TEG was directly attached onto an alumina tube, which achieved a maximum output voltage of 27.0 mV and a maximum power of 1.62 mW at ∆T = 39 K. The output power density was 1.42 mW cm -2 at the same temperature difference.…”
Section: Shape Conformal Tegmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6(a) illustrates the fabrication process of the conformal TEG and demonstrates how 3D printing was employed to produce semicircular shapes corresponding to the cylindrical heat source. Several studies have reported the production of such conformal TEGs [32,42,52,55,71,95], with a representative example being the work by Kim et al [32], who created cylindrical TEGs with dispenser-printed n-and p-type half-rings using an all-inorganic TE ink (figure 6(b)). The TEG was directly attached onto an alumina tube, which achieved a maximum output voltage of 27.0 mV and a maximum power of 1.62 mW at ∆T = 39 K. The output power density was 1.42 mW cm -2 at the same temperature difference.…”
Section: Shape Conformal Tegmentioning
confidence: 99%
“…Similarly, Su et al [52] manufactured annular devices through dispenser printing using a TE ink containing an organic binder, resulting in an output voltage of 60.8 mV and a maximum output power of 0.68 mW at ∆T TE = 54.6 K. This result is consistent with the FEM simulation results (figure 6(c)). Subsequently, Wang et al [95] also produced half-angular legs with a quasi-inorganic TE ink using dispenser printing, and the devices achieved an output voltage of 40.61 mV and a power output of 0.38 mW at ∆T TE = 55 K (figure 6(d)). In addition to dispenser printing, Hu et al [71] manufactured shape-conformal TEGs using SLM technology (figure 6(e)).…”
Section: Shape Conformal Tegmentioning
confidence: 99%
“…Employing charge control and framework reinforcement strategies, materials with high figure-of-merit ZT values of 0.65 for p-type and 0.53 for n-type were obtained. Furthermore, the research team used low concentrations of organic binders PAA and PEI to form stable hybrid structures through electrostatic interactions and steric hindrance, thus dispersing Bi Te -based TE particles, as illustrated in Figure 4 d. Concurrently, a second-phase interfacial welding technique was applied, using a liquefied phase to fill the interparticle voids, enhancing the electrical interconnections between particles [ 100 ]. Eunhwa Jang and colleagues [ 95 ] combined commercially available p-type BST particles, natural n-type Bi particles, and chitosan binder to formulate a TE composite ink.…”
Section: Ink-based Tegsmentioning
confidence: 99%
“…( d ) Schematic illustration of the stable hybrid structure formed by PAA and PEI with Bi Te -based TE particles. Reprinted with permission from [ 100 ]. Copyright 2022, Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…[28,29] Among additive manufacturing processes, direct ink writing (DIW), which is a class of omnidirectional printing, is one of the most promising fabrication technologies and offers high customizability to realize directly printable TEGs with 3D arbitrary shapes and structures. [30][31][32][33][34] In addition, DIW enables the printing of complex 3D structures using a broad set of materials for nozzle extrusion, ranging from inorganic TE materials to conductive polymers, by regulating their rheological properties. [32,[34][35][36][37] Therefore, DIW technology presents a breakthrough to overcome the limitations of conventional additively manufactured TEGs by directly printing 3D TE legs that transfer heat in the throughplane direction.…”
Section: Introductionmentioning
confidence: 99%